2016
DOI: 10.1016/j.meegid.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history and spatiotemporal dynamics of DENV-1 genotype V in the Americas

Abstract: The genotype V has been the most prevalent dengue virus type 1 (DENV-1) clade circulating in the Americas over the last 40years. In this study, we investigate the spatiotemporal pattern of emergence and dissemination of DENV-1 lineages in the continent. We applied phylogenetic and phylogeographic approaches to a comprehensive data set of 836 DENV-1 E gene sequences of the genotype V isolated from 46 different countries around the world over a period of 50years (1962 to 2014). Our study reveals that genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
8
26
0
Order By: Relevance
“…The time-scaled Bayesian MCC tree shows the origin and spread of DENV-1 genotype V. We observed two well-supported and independent introductions of DENV from the Asian region (Indian sequences are the most likely ancestral ones) to Brazil, Venezuela, Colombia, and Argentina (Clade I, highlighted in red), one from India to Brazil (Clade II, highlighted in green), and the last one from India to Brazil and Argentina passing through the British Virgin Islands (Tortola, Caribbean region) belonging to Clade III (highlighted in blue) ( Figure 2(a) ). Our data on DENV-1 genotype V (the most prevalent genotype circulating in the Americas), agree partly with Bruycker-Nogueira et al [ 51 ], in that all DENV-1 genotype V sequences from South America investigated in this study have an ancient Asian origin. However, we suggest three independent introductions into South America with at least one in Tortola, one of the largest and most populated Islands in the Caribbean ( Figure 2(a) ).…”
Section: Resultssupporting
confidence: 92%
“…The time-scaled Bayesian MCC tree shows the origin and spread of DENV-1 genotype V. We observed two well-supported and independent introductions of DENV from the Asian region (Indian sequences are the most likely ancestral ones) to Brazil, Venezuela, Colombia, and Argentina (Clade I, highlighted in red), one from India to Brazil (Clade II, highlighted in green), and the last one from India to Brazil and Argentina passing through the British Virgin Islands (Tortola, Caribbean region) belonging to Clade III (highlighted in blue) ( Figure 2(a) ). Our data on DENV-1 genotype V (the most prevalent genotype circulating in the Americas), agree partly with Bruycker-Nogueira et al [ 51 ], in that all DENV-1 genotype V sequences from South America investigated in this study have an ancient Asian origin. However, we suggest three independent introductions into South America with at least one in Tortola, one of the largest and most populated Islands in the Caribbean ( Figure 2(a) ).…”
Section: Resultssupporting
confidence: 92%
“…The Sub-Clade Ia had Argentina as the gateway to Brazil, spreading to the Northeast, Midwest and Southeast regions of the country. The observation of Argentina as an ancestor for the Brazilian strains, corroborate our previous study 15 . With the introduction in the Southeast region, we observed most of the dispersions of the viral strain within Brazil, as well as returning to Argentina, which circulated at least until 2016.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the differences in the origins of Ecuadorian viruses, all our analyses indicated that Venezuela and Colombia to this day remain contributors of dissemination of dengue across this region of South America. This dissemination started already in the early 1990s, and has resulted in introduction and reintroduction of DENV1 and DENV2 into several countries of both South and North America, including Colombia, Argentina, Nicaragua, Puerto Rico, Brazil and Ecuador, resulting in sustained DENV spread in these countries [38][39][40]. The potential of dengue export from Venezuela over long distances has also been previously observed [41].…”
Section: Discussionmentioning
confidence: 70%
“…However, more recent findings suggest that CHIKV infections are found close to the country borders, suggesting that CHIKV might have started following the patterns of dengue spread in this region [44]. Indeed, dengue, like CHIKV, was introduced into South America mainly through the Caribbean [40,45,46]. Given that these two pathogens share the common vector, Ae.…”
Section: Discussionmentioning
confidence: 99%